1992
DOI: 10.1002/jlb.51.6.570
|View full text |Cite
|
Sign up to set email alerts
|

Defective lipopolysaccharide-induced production of both interleukin 1α and interleukin 1β by A/J mouse macrophages is posttranscriptionally regulated

Abstract: Interleukin 1 (IL-1) production by A/J (A) and C57BL/6J (B6) mouse peritoneal macrophages stimulated with lipopolysaccharide (LPS) was determined. Strain A macrophages produced low levels of soluble IL-1 bioactivity compared with B6 macrophages. This defect was not reversed by indomethacin, interferon-gamma, phorbol myristate acetate, or calcium ionophore A23187. In contrast, cytosolic IL-1 bioactivity was similar in LPS-stimulated A and B6 macrophages. Western blotting revealed that A macrophage supernatants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…These two strains of mice did not differ in expression of mRNA for TNF-a, IL-la, IL-2, and IL-4 in either the spleen or liver, as assessed by both RT-PCR analysis and in situ hybridization. Our results are consistent with a report that macrophages from C57BL/6 and ANJ mice do not differ in their ability to transcribe IL-la and IL-1,B mRNA in response to lipopolysaccharide stimulation in vitro (1). Semiquantitative analysis with 32P-labelled oligonucleotide probes indicated that the resistant C57BL/6 mice expressed greater amounts of IFN--y and GM-CSF mRNAs in the spleen than did susceptible A/J mice (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…These two strains of mice did not differ in expression of mRNA for TNF-a, IL-la, IL-2, and IL-4 in either the spleen or liver, as assessed by both RT-PCR analysis and in situ hybridization. Our results are consistent with a report that macrophages from C57BL/6 and ANJ mice do not differ in their ability to transcribe IL-la and IL-1,B mRNA in response to lipopolysaccharide stimulation in vitro (1). Semiquantitative analysis with 32P-labelled oligonucleotide probes indicated that the resistant C57BL/6 mice expressed greater amounts of IFN--y and GM-CSF mRNAs in the spleen than did susceptible A/J mice (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Data are mean ± standard error of the mean. ***P < .001, **P < .01, *P < .05 (n ≥ 3 for all groups) present with decreased neutrophil infiltration and diminished acute inflammation, and macrophages from A/J mice express lower levels of interleukin-1 compared with C57BL/6J mice, 27,28 which is consistent with the reduced neutrophil counts observed in A/J mice compared with C57BL/6J mice in the present study after development of PI. As a result of inherent immune and inflammatory host-response differences, and their resistance and susceptibility to PI, A/J, C3H/HeJ and C57BL/6J mice make suitable animal models for understanding the genetic differences that contribute to PI.…”
Section: Discussionsupporting
confidence: 87%
“…24 In our study, the distinct responses to experimental PI observed among the different strains are most probably a result of inherent differences in immune response and bone modeling/remodeling. For instance, the antagonistic phenotypes observed in A/J and C57BL/6J mice have already been evaluated in many systems, including neutrophil physiology, the inflammatory infiltrate response and the mac- present with decreased neutrophil infiltration and diminished acute inflammation, and macrophages from A/J mice express lower levels of interleukin-1 compared with C57BL/6J mice, 27,28 which is consistent with the reduced neutrophil counts observed in A/J mice compared with C57BL/6J mice in the present study after development of PI. As a result of inherent immune and inflammatory host-response differences, and their resistance and susceptibility to PI, A/J, C3H/HeJ and C57BL/6J mice make suitable animal models for understanding the genetic differences that contribute to PI.…”
Section: Discussionmentioning
confidence: 99%